SPE/TLC/Densitometric Quantification of Selected Synthetic Food Dyes in Liquid Foodstuffs and Pharmaceutical Preparations - Anna W. Sobańska; Jarosław Pyzowski; Elżbieta Brzezińska (Journal of Analytical Methods in Chemistry)
Selected synthetic food dyes (tartrazine, Ponceau 4R, Brilliant Blue, orange yellow, and azorubine) were isolated from liquid preparations (mouthwashes and beverages) by Solid Phase Extraction on aminopropyl-bonded silica with diluted aqueous sodium hydroxide as an eluent. The extraction step was followed by thin layer chromatography on silica gel 60 with chloroform-isopropanol-25% aq. ammonia 1 : 3 : 1 (v/v/v) as mobile phase and the densitometric quantification of dyes was achieved using quadratic calibration plots (R2>0.997; LOQ = 0.04–0.09 μgspot−1). The overall recoveries for all studied dyes were at the average level of over 90% and the repeatability of the proposed procedure (CV ≤ 4.1%) was sufficient to recommend it for the routine quantification of the aforementioned dyes in liquid matrices.